(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, one of the leading representatives of Uzbek literature, Abdulla Oripov, published posthumously, the poetry collection "Birth of the Poet", shows that the development of the poet’s poetic thinking is greatly influenced by folk art. and the original creator brings a new approach and outlook to literature without denying the tradition before him, which serves the development of fiction. In addition, at the core of folk art there are unique values, mentality, and way of thinking of a certain people, so it is said that inspiration from ancient chants and deep roots is characteristic of all artists.